Measurement properties of patient-reported outcome measures (PROMs) in patients with hyperhidrosis: protocol for a systematic review - Michaela Gabes (Systematic Reviews, 2021)
Abstract Background Hyperhidrosis is a chronic skin condition that impairs the patient’s quality of life (QoL). There are several patient-reported outcome measures (PROMs) for patients affected by hyperhidrosis available; however an evidence-based assessment of their quality has not been undertaken so far. Objective In our systematic review, we aim to identify all existing PROMs that were developed and/or validated for measuring patient-reported outcomes in patients with hyperhidrosis and assess their measurement properties in a transparent and structured way to give a recommendation for future clinical research. Methods/design Our systematic review aims to contain all PROMs developed and/or validated for patients with hyperhidrosis. We will perform a highly sensitive, systematic literature search including the databases MEDLINE (Ovid), EMBASE (Ovid), and Science Citation Index Expanded and Social Sciences Citation Index (Web of Science). Especially studies which evaluate, describe, or compare measurement properties of PROMs for patients with hyperhidrosis will be considered as eligible. Two independent reviewers will judge the eligibility of the studies found in the literature search. The study and PROM characteristics will be summarized in evidence tables. The methodological quality of each study will be assessed using the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) Risk of Bias checklist. We will apply predefined and consensus-based quality criteria for good measurement properties. Subsequently, the quality of the evidence will be graded. Furthermore, aspects on interpretability and feasibility will be described. A final recommendation will be given. Discussion In our systematic review, we aim to provide a comprehensive description of the quality of all existing PROMs for patients with hyperhidrosis. The assessment of measurement properties, interpretability, and feasibility will serve as a guidance regarding the selection of PROMs for future clinical hyperhidrosis trials. Systematic review registration PROSPERO CRD42020170247